Development of Virtual Teamwork Skills for Distance Students through Simulated Global Virtual Team Projects - Pienaar, J.; Wu, Peng; Adams, N. (2016)
Many Australian universities are pushing the use of distance education in delivering construction programs. However, recent accreditations show that the development of teamwork skills, one core graduate attribute, is not satisfactory in these programs. A case study is therefore adopted to investigate the effectiveness of using simulated global virtual team (SGVT) projects to teach virtual teamwork skills at Central Queensland University (CQU) which offers the construction education program exclusively by distance education. The findings suggest that SGVT projects can help increase the level of engagement and benefit the students through the involvement of experienced practitioners. More importantly, with the increased level of engagement, distance students can develop nondiscipline-oriented teamwork skills, e.g., collaboration and leadership, through the distinct roles they play in the SGVT projects. The results provide good guidance and will be useful for universities and institutions which are seeking to implement distance education in construction education.